NASKAH PUBLIKASI ILMIAH ANALISIS YURIDIS TERHADAP IMPLEMENTASI ASAS PERADILAN SEDERHANA, CEPAT DAN BIAYA RINGAN DALAM PENYELESAIAN PERKARA PERDATA (Studi di Pengadilan Negeri Singkawang). - NOVITA RIAMA NPM. A.21208069, Jurnal Mahasiswa S2 (Jurnal NESTOR Magister Hukum, 2013)
ABSTRACTThis thesis studies raise the issue of "Analysis of Implementation Principle Against Judicial Justice Simple, Quick And Cost Lightweight In Civil Case Settlement (Studies In Court Singkawang)".This study uses sociological approach to normative research. The survey results revealed that the principle of justice is simple, fast and low cost have not been fully realized in the completion of civil cases in the District Court Singkawang as there are in excess of the settlement period of 6 (six) months. In 2008 to 2010 civil lawsuit suit filed in state court Singkawang 40 (forty) files and as many as 13 (thirteen) file completed in more than 6 (six) months with an average case cost over one million dollars. In Article 2 paragraph (4) of Law No. 48 of 2009 on Judicial Power stated that Justice be done with a simple, fast, and low cost. Then the explanation stated that what is meant by "simple" is the examination and settlement is done by efficiently and effectively. The definition of "low cost" is the cost of the case that are accessible to the public. However, the principle is simple, fast, and low cost in the investigation and resolution of cases in court does not rule accuracy and precision in the search for truth and justice. In the Guidelines on Duties and Administrative Tribunal, in Part Two of the Technical Affairs for the General Court confirmed that Civil Case civil cases heard and ruled must be completed within 6 (six) months, either in the District Court and the Court of Appeal. Related to the principle of justice is done by a simple, rapid, and low cost, the Supreme Court through a Circular Letter (SEMA) No. 6 of 1992 on Settlement of Cases in the High Court and the District Court affirmed that the settlement must be interrupted and completed within 6 (six) months. In fact there are settlements that cut through 6 (six) months, so the Supreme Court issued Circular No. 3 of 1998 on Settlement Case among others assert that matters should be decided in court and be completed within 6 (six) months including minutasi, the general civil matters, civil and administrative matters of religion and state, but due to the nature and circumstances of his case had more than 6 (six) months, provided that the Chairman of the Court of first instance concerned shall report the reasons to the Chairman of the Court of Appeal . Particular emphasis on the settlement of civil cases must be completed within 6 (six) months is also confirmed in the Supreme Court Decision on Standards No. 026/KMA/SK/II/2012 Judicial Service, which states that the court shall conduct proceedings (lawsuits, answers, replik, closing argument, evidence, conclusions, decisions, minutasi) were completed within a period not later than 6 (six) months since the case is filed. Settlement of civil cases that exceed a period of 6 (six) months may lead to higher legal costs. Costs associated with the case, the Supreme Court Decision on Standards No. 026/KMA/SK/II/2012 Judicial Service has stated that the amount of down-payment fees at every court established by Decree of the President of the Court and the determination of the size of the down payment of court fees civil, civil religion and state administration based on the number of litigants close and far distance to where the called party and administrative costs, which are accounted for in the decision. In this case the District Court Singkawang determine the amount of down-payment of court fees and the cost of the call/notice by thejoint decision of the Chairman and the Chairman of the Religious Bengkayang Singkawang Court Number: W14 A8/135/HK. 05/I/2012 and W17-A8/63/HK.00.8/I/2012 dated January 14,2012. Factors that led to the principle of justice is simple, fast and low cost have not been fully realized in the settlement of civil cases in the District Court Singkawang is the absence of the parties on the day of the trial which has been set; many witnesses to be presented by the parties and witnesses or evidence are often delayed; the parties do not comply with the provisions regarding pay matters; defendant deliberately delaying the trial for the purpose of enlarging plaintiff's expense; many plaintiffs and defendants, so the examination and proof (especially of witnesses the parties) require longer periods of time, as well as judges and administration of justice such as the length of deliberation to make decisions. The recommendations given are that the disputing parties in a civil case in the District Court should have the will Singkawang, seriousness and good faith to resolve the dispute in compliance with all provisions of the proceedings in court to dispute can be resolved quickly. It takes a standard down payment rules on legal costs in the district court, so there is no uniformity regarding the down payment of court fees in all courts in Indonesia. There should be strict rules to limit delay the trial in order to avoid the possibility of the parties repeatedly requested postponement resulting civil settlement process becomes longer and court costs to be great. There should also be strict rules regarding rewards and sanctions for judges related to the settlement with respect to the characteristics of cases handled.